Polyamide composite material as well as preparation method and application thereof

Through the design of polyamide composite materials, the combination of PA6 resin, polyadipyl isophthalamine and silsesquioxane is used to form a cross-linked structure, which solves the problem of insufficient barrier properties and mechanical properties of hydrogen storage bottle materials. It achieves efficient gas barrier and impact resistance, and is suitable for the inner lining of hydrogen storage bottles, simplifies production processes and improves safety.

CN119242028APending Publication Date: 2025-01-03KINGFA SCI & TECH CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411322330.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The plastic lining materials of existing hydrogen fuel cell vehicle-mounted hydrogen storage bottles have poor barrier properties and mechanical properties, complex preparation process and are not suitable for use in high-pressure and high-temperature environments, resulting in insufficient performance of hydrogen storage cylinders and affecting the mileage and safety of the car.

Method used

Polyamide composite materials, including PA6 resin, polyadipyl isophthalamine and silsesquioxane, improve impact resistance and gas barrier effect through physical and chemical mesh crosslinking structures, and simplify the preparation process To suit industrial production.

Benefits of technology

It realizes the high mechanical properties and excellent gas barrier properties of polyamide composite materials, and is suitable for the barrier layer of hydrogen storage bottles, simplifies processing technology, reduces energy consumption, and improves the overall performance and safety of hydrogen storage bottles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005054347780000031
    Figure BDA0005054347780000031
  • Figure BDA0005054347780000062
    Figure BDA0005054347780000062
  • Figure BDA0005054347780000071
    Figure BDA0005054347780000071
Patent Text Reader

Abstract

The invention discloses a polyamide composite material as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. In the polyamide composite material disclosed by the invention, MXD6, silsesquioxane and PA6 are mutually matched to synergistically improve the mechanical property and barrier effect of the polyamide composite material, and the polyamide composite material is suitable for being applied to preparation of a barrier layer of a hydrogen storage bottle and a high-toughness automobile wire harness part.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer alloy materials, and in particular to a polyamide composite material and a preparation method and application thereof. Background Art

[0002] Hydrogen fuel cells are considered to be the ideal mobile power source in the 21st century due to their high efficiency and zero emissions. Hydrogen is the lightest substance in the universe and is flammable and explosive. It is very difficult to achieve safe high-density storage, which has been considered one of the main obstacles to the development of hydrogen fuel cell vehicles. So far, high-pressure gas storage is considered to be the most practical storage method for the on-board application of hydrogen fuel cells. The development of safe high-pressure on-board hydrogen supply technology has always been an important part of the research and development of hydrogen fuel cell vehicles. The high-pressure hydrogen storage bottles used for high-pressure gas storage are generally composite materials and usually need to work under high pressure and high temperature environments, which puts higher requirements on the physical and mechanical properties, reliability and economy of the composite materials.

[0003] The pressure of hydrogen stored in vehicle-mounted composite gas cylinders will directly determine the mileage of the vehicle. At present, the research and production of 35MPa third-generation metal-lined composite materials for hydrogen storage cylinders in China are mainly limited to that of foreign 70MPa fourth-generation plastic-lined composite gas cylinders (IV-type gas cylinders). The key and difficulty of the development of IV-type gas cylinders lies in the development of plastic linings. According to domestic and foreign reports, materials such as HDPE, PA6 and PET can be used for plastic linings. However, the barrier properties and mechanical properties of hydrogen in plastic linings have always been the focus and hotspot of research.

[0004] The existing scheme is to adopt a multi-layer barrier scheme, which has low production efficiency. For example, CN113124309A adopts a multi-layer rotational molding process and feeds materials multiple times to prepare a 5-layer hydrogen storage bottle liner. The outer and inner layers are polyamide, polyester or high-density polyethylene; the barrier layer is ethylene-vinyl alcohol copolymer or its modified product; the inner / outer transition layer is a mixture of the material used for the inner / outer layer and ethylene-vinyl alcohol copolymer (EVOH). Although this plastic liner has good water vapor and hydrogen barrier properties, the preparation process is complicated, and the barrier performance of EVOH is greatly affected by humidity and temperature changes. CN115785508A forms a bottle structure by injection molding of chlorinated polyvinyl chloride resin (CPVC), and then coats polyvinylidene chloride (PVDC) resin on the inner or outer surface of the bottle structure formed by CPVC resin, and dries and matures to obtain a hydrogen storage bottle. Although PVDC also has excellent barrier properties, it is not suitable for gas storage bottle liners that are in direct contact with hydrogen because the residual trace chlorine will react with hydrogen.

[0005] Therefore, there is still a need to develop a single-layer barrier material for hydrogen cylinders with good barrier properties and mechanical properties. Summary of the invention

[0006] Based on the defects of the existing technology in that the barrier properties and mechanical properties of the multilayer hydrogen storage cylinder liner materials are poor, the purpose of the present invention is to provide a polyamide composite material and a preparation method and application thereof.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A polyamide composite material comprises the following components in parts by weight:

[0009] 39-71 parts of PA6 resin, 18-51 parts of poly(m-phenylenediamine adipamide) (MXD6), 0.5-11 parts of silsesquioxane, 6-22 parts of toughening agent, and 0.2-1.1 parts of auxiliary agent.

[0010] In the scheme of the present invention, silsesquioxane has a spherical network structure and carries reactive groups such as epoxy groups. The reactive groups carried by silsesquioxane are bonded to the end groups of resins (PA6, MXD6) to form a physical and chemical network cross-linked structure, which can improve the compatibility between POSS and polymers, enhance impact resistance and increase gas barrier effect. MXD6, silsesquioxane and PA6 cooperate with each other to synergistically increase the mechanical properties and barrier effect of polyamide composite materials.

[0011] Preferably, the polyamide composite material comprises the following components in parts by weight: 40-70 parts of PA6 resin, 20-50 parts of poly(m-phenylenediamine adipamide), 1-10 parts of silsesquioxane, 7-20 parts of toughening agent, and 0.2-1 part of auxiliary agent.

[0012] PA6 resin is obtained by ring-opening polymerization of caprolactam. It is a semi-crystalline polymer. The repeated amide groups in its molecular chain can be hydrogen-bonded and regularly arranged to form crystals, thereby giving polyamide products good mechanical properties and oil and solvent resistance, self-lubrication and certain flame retardancy. At the same time, it has the characteristics of low melting point and easy molding and processing. It can be better matched with poly(m-phenylenediamine adipamide) and silsesquioxane. There is no special requirement for its viscosity. For example, PA6 resin with a relative viscosity of 1-4 can be selected, and PA6 resin with a relative viscosity of 2.0-3.8 can also be preferred. The viscosity test method is ISO 307-2019.

[0013] MXD6 is synthesized by the condensation of meta-phenylenediamine and adipic acid. It is a crystalline semi-aromatic special nylon resin. It has the lowest water absorption rate among nylon materials, small dimensional change after water absorption, and less reduction in mechanical strength. It can enhance the gas barrier effect of polyamide composites and improve the mechanical properties of polyamide composites. There is no special requirement for its viscosity. For example, MXD6 with a relative viscosity of 1-4 can be selected, and MXD6 with a relative viscosity of 2.1-2.3 can also be preferred. The viscosity test method is ISO 307-2019.

[0014] Preferably, the mass ratio of the PA6 resin to poly(m-xylylene adipamide) is (0.8-3.5):1.

[0015] Further preferably, the mass ratio of the PA6 resin to poly(m-xylylene adipamide) is (1-3):1.

[0016] The mass ratio of PA6 resin to poly(m-xylylene adipamide) can be (0.8:1), (1:1), (1.5:1), (2:1), (2.5:1), (3:1), (3.5:1), etc., as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0017] PA6 resin and MXD6 are the matrix resins that account for a relatively large proportion in the product of the present invention. The sum of the mass percentages of PA6 resin and MXD6 in the polyamide composite material is not less than 55%. The mass ratio of PA6 resin to MXD6 will affect the barrier properties, impact resistance and processing properties of the product. It has been verified that when the PA6 resin and MXD6 in the product are preferably within the above range, the product can obtain the best barrier properties and impact resistance properties.

[0018] Preferably, the molecular formula of the silsesquioxane is (RSiO 3 / 2 ) n , wherein n is an even number, n≥2, such as in the following structural formula, n is 6, 8 and 10 respectively, preferably n is 6-20; R includes at least one of epoxy, ether, hydroxyl, phenyl and vinyl, and is a typical polyhedral oligomeric silsesquioxane, also known as

[0019]

[0020] Make POSS.

[0021] More preferably, R is any one of epoxy, ether and hydroxyl groups. Such groups have high reactivity and can react with groups in nylon to provide barrier and impact resistance properties of the product.

[0022] More preferably, the molecular weight of the silsesquioxane is 400-3000 g / mol, and more preferably 1300-3000 g / mol, and the molecular weight is characterized by gel permeation chromatography using N,N-dimethylformamide as the eluent.

[0023] Preferably, the weight portion of the silsesquioxane is 2-8 parts.

[0024] The weight percentage of silsesquioxane can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, etc., as well as specific percentages between the above percentages. Due to the limited space and simplicity, the present invention will no longer exhaustively list the specific percentages included in the above ranges. Silsesquioxane is an important component for increasing the impact resistance and gas barrier effect of polyamide composite materials. Its addition amount affects the impact resistance and gas barrier effect of polyamide composite materials. Within the above weight percentage content range, the impact resistance and gas barrier performance of polyamide composite materials are better.

[0025] Preferably, when R of the silsesquioxane includes an epoxy group, the epoxy equivalent of the silsesquioxane is in the range of 50-250 g / mol, preferably 160-180 g / mol.

[0026] Preferably, the toughening agent includes a maleic anhydride graft, and the maleic anhydride graft includes at least one of maleic anhydride grafted polyethylene (MAH-g-PE), maleic anhydride grafted modified polyolefin elastomer (MAH-g-POE), and maleic anhydride grafted ethylene propylene diene rubber (MAH-g-EPDM). A maleic anhydride graft with a grafting rate of 0.1-1.5% can be selected, and the grafting rate of the maleic anhydride graft is measured by acid-base titration.

[0027] Preferably, the auxiliary agent includes an antioxidant and a lubricant.

[0028] More preferably, the auxiliary agent includes 0.2 to 0.5 parts of antioxidant and 0.2 to 0.5 parts of lubricant.

[0029] More preferably, the antioxidant comprises a compound of a hindered phenol antioxidant and a phosphite antioxidant; and the lubricant comprises at least one of silicone, ester, amide, polyethylene, stearic acid, and fatty acid lubricants.

[0030] Preferably, the hindered phenol antioxidant is selected from at least one of antioxidant 1098, antioxidant 1010, antioxidant 1076, and antioxidant 3114; and the phosphite antioxidant is selected from at least one of antioxidant 168 and antioxidant PEP-36.

[0031] Another object of the present invention is to provide a method for preparing the polyamide composite material, comprising the following steps:

[0032] The components are mixed uniformly, and then melt-kneaded, extruded and granulated to obtain the polyamide composite material.

[0033] The preparation method of the product of the present invention has simple operation steps and can realize industrial-scale production.

[0034] Preferably, the temperature of the melt mixing is 200-250° C., and the rotation speed is 200-600 rpm.

[0035] Another object of the present invention is to provide an application of the polyamide composite material in the preparation of a hydrogen storage bottle.

[0036] The polyamide composite material of the present invention has mechanical impact resistance and barrier properties, can be directly used in the preparation of the barrier layer of the hydrogen storage bottle, can be injection molded in one step, and compared with the multi-layer liner, the processing technology is simple and the energy consumption is low, which is very consistent with the application requirements of the inner lining layer of the hydrogen storage bottle.

[0037] The beneficial effect of the present invention is that in the polyamide composite material of the present invention, MXD6, silsesquioxane and PA6 cooperate with each other to synergistically improve the mechanical properties and barrier effect of the polyamide composite material, and is suitable for use in preparing the barrier layer of hydrogen storage bottles and high-toughness automotive wiring harnesses. DETAILED DESCRIPTION

[0038] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0039] Examples 1 to 17 and Comparative Examples 1 to 5

[0040] The preparation methods of Examples 1-17 and Comparative Examples 1-5 of the present invention are as follows:

[0041] (1) Prepare the raw materials for extrusion according to the components and weight proportions in Tables 1 and 2;

[0042] (2) The PA6 resin, MXD6, silsesquioxane, toughening agent, antioxidant and lubricant prepared in (1) are mixed evenly in a high-speed mixer and then added into a twin-screw extruder for melt mixing. The resin is evenly dispersed in the extruder, extruded and granulated to obtain the material. The temperatures of screw zones 1 to 10 on the extruder screw are 80, 230, 250, 250, 240, 230, 200, 200, 200, 200, 240° C., respectively, and the rotation speed is 300 rpm;

[0043] Among them, in comparative example 5, MXD6 is replaced by PA10T, and the rest of the process is the same.

[0044] Information on raw materials involved:

[0045] PA6 resin: HY-2800A Jiangsu Haiyang Chemical Fiber Co., Ltd., relative viscosity 2.8;

[0046] MXD6 resin: ZYMX5006, Sinochem International (Holdings) Co., Ltd., relative viscosity 2.3;

[0047] Polydecane terephthalamide (PA10T): Vicnyl 700 Kingfa Technology Co., Ltd.;

[0048] Polyborosiloxane: Self-made, dissolve sodium borate in a certain amount of water, then slowly drip dichlorosilane at room temperature, stir and react for 3 hours, remove the solvent, add hydroxy silicone oil to the dried product, and react for 4 to 6 hours to obtain polyborosiloxane; by adjusting the molar ratio of sodium borate and hydroxy silicone oil, a borosiloxane sample with a boron to silicon molar ratio of 1:100 is obtained;

[0049] Hydroxyl silicone oil: viscosity 500cSt, degree of polymerization about 106, West Asia reagent;

[0050] Sodium borate: analytical grade, Sinopharm reagent;

[0051] Dichlorosilane: relative molecular mass 191, Sinopharm Reagent;

[0052] Antioxidants: hindered amine antioxidant 1098 and phosphite antioxidant PEP-36, commercially available;

[0053] Lubricant, polyethylene wax, commercially available;

[0054] Toughening agent: POE-g-MAH: KT-915, Shenyang Ketong Plastic Co., Ltd., grafting rate 0.8%;

[0055] Silsesquioxane 1-1 (epoxy): Octa-epoxycyclohexylethyl cage polysilsesquioxane, POSS1010, Guangzhou Yixin Technology Co., Ltd., molecular weight 1418 g / mol;

[0056] Silsesquioxane 1-2 (epoxy): tetracyclosiloxane, Mercapto Chemical, molecular weight 697.1 g / mol;

[0057] Silsesquioxane 1-3 (epoxy): Cage-type octa(eugenol epoxydimethylsiloxy) silsesquioxane (8EUEP-POSS) was prepared by the reaction of 8H.POSS with eugenol epoxy. The specific preparation process can be referred to the reference "Preparation and performance study of functionalized cage-type oligomeric silsesquioxanes and their application in hybrid materials (Zhang Xianwei, Zhejiang University, 2020)" in "3.2.9 Synthesis of 8EUEP-POSS", molecular weight 2815 g / mol;

[0058] Silsesquioxane 2 (hydroxy): trihydroxysilsesquioxane, molecular weight 678g / mol, homemade, specific method: add 433mL acetone to a three-necked flask, add 22g cyclopentyltrichlorosilane, slowly add 120mL distilled water while stirring, heat reflux reaction for 65h, vacuum filter the product and rinse with acetone to obtain a crude product, dissolve the crude product in 20 times pyridine, extract with diethyl ether to obtain trihydroxysilsesquioxane, molecular weight 678g / mol;

[0059] Silsesquioxane 3 (epoxy and ether groups): octa[3-(glycidyl ether)propyl] cage-type polysilsesquioxane, molecular weight 1338 g / mol, Reith reagent;

[0060] Silsesquioxane 4(phenyl): poly(dimethylsiloxane-co-methylphenylsiloxane), molecular weight 409 g / mol, Macklin reagent;

[0061] Silsesquioxane 5 (vinyl): vinyldimethylsiloxy cage polysilsesquioxane, POSS1016, molecular weight 1226 g / mol, Guangzhou Yixin Technology Co., Ltd.;

[0062] Other chemical reagents used in polymerization were purchased from Sinopharm.

[0063] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0064] Table 1

[0065]

[0066]

[0067] Table 2

[0068]

[0069] In order to verify the performance of the polyamide composite material of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:

[0070] (1) Mechanical properties: According to ISO527-1 / 2-2019 standard, an injection molding machine was used to make a 4 mm thick test specimen with a size of 175*10*4 mm. The tensile strength of the test specimen was tested at 23°C and a test speed of 5 mm / min. At the same time, the simply supported beam notched impact strength of the dry specimen at 23°C was tested according to ISO179 / 1eA.

[0071] (2) Gas permeability evaluation method

[0072] Refer to GB / T 1038-2022 standard, after loading the sample into the test bench, ensure that the gas source valve and vent valve are closed, open the high-pressure valve, low-pressure valve and isolation valve at the same time, turn on the vacuum pump to make the gas path as vacuum as possible, and the pressure sensor value remains unchanged after several hours. At this time, close the isolation valve and open the gas source valve to allow the test gas to enter the high-pressure chamber, and continue to increase the vacuum degree of the low-pressure chamber, and keep the connection between the vacuum pump and the low-pressure chamber to keep the pressure reading constant. The hydrogen in the high-pressure chamber will penetrate through the membrane into the low-pressure chamber. After closing the isolation valve and the low-pressure chamber valve, the test begins, and the relationship between pressure and time is recorded. In the stable gas permeation stage, the pressure change rate is positively correlated with the gas permeability. The hydrogen permeability is calculated according to the following formula:

[0073]

[0074] In the formula, Q g is the gas permeability of the material, ΔP / Δt is the pressure change rate at stable permeability, V is the volume of the low-pressure chamber, S is the test area of ​​the sample, T is the test temperature, P 1 -P 2 is the pressure difference on both sides of the sample, T o , P o is the temperature (273.15K) and pressure (1.013×105Pa) under standard conditions, D is the sample thickness, this batch was tested using hydrogen gas, and D=1mm, T=23℃.

[0075] The test results are shown in Table 3.

[0076] Table 3

[0077]

[0078] As can be seen from Table 3, the tensile strength, impact strength and hydrogen barrier property of the polyamide of the present invention are relatively high, and the tensile strength reaches 40-62KJ / m 2 , impact strength can reach 15-60KJ / m 2 , hydrogen permeability is as low as 1.9-3.6 (10 -11 cm 3 cm / (cm2 ·s·Pa)).

[0079] It can be seen from Examples 1 to 5 that the mass ratio of PA6 and MXD6 has an effect on the mechanical and barrier properties of the polyamide composite material. When the PA6 / MXD6 mass ratio is 0.8-3.5, good mechanical properties and gas barrier properties can be maintained. The preferred PA6 / MXD6 mass ratio is (1-3): 1. At this time, the gas barrier properties of the polyamide composite material are better.

[0080] From Examples 1, 6 to 9 and Comparative Example 4, it can be seen that the weight of silsesquioxane added can be selected to be 1-10 parts, preferably 2-8 parts. Too much will lead to excessive cross-linking of the material, increase its brittleness and reduce the elongation at break of the material. When subjected to air pressure, the material is prone to breakage, thereby reducing the barrier performance.

[0081] It can be seen from Example 1 and Comparative Examples 1-3 that silsesquioxane and MXD6 resin synergize with each other to improve the impact strength and gas barrier properties of the material.

[0082] It can be seen from Example 1 and Comparative Example 5 that both poly(decanediamine terephthalamide) (PA10T) and poly(meta-phenylene adipamide) (MXD6) belong to nylon resins. Compared with poly(decanediamine terephthalamide) (PA10T), only poly(meta-phenylene adipamide) (MXD6), a substance with a unique chemical structure, can cooperate with silsesquioxane and PA6 to synergistically increase the mechanical properties and barrier effect of the polyamide composite material.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A polyamide composite material, characterized in that: The composition comprises the following components in parts by weight: 39-71 parts of PA6 resin, 18-51 parts of poly(m-phenylenediamine adipamide), 0.8-11 parts of silsesquioxane, 6-22 parts of toughening agent, and 0.1-1.1 parts of auxiliary agent.

2. The polyamide composite material according to claim 1, characterized in that: The molecular formula of the silsesquioxane is (RSiO3 / 2) n , wherein n is an even number, and R includes at least one of an epoxy group, an ether group, a hydroxyl group, a phenyl group, and a vinyl group.

3. The polyamide composite material according to claim 2, characterized in that: The molecular weight of the silsesquioxane is 400 to 3000 g / mol.

4. The polyamide composite material according to claim 1, characterized in that: The mass ratio of the PA6 resin to poly(m-phenylenediamine adipamide) is (0.8-3.5):

1.

5. The polyamide composite material according to claim 1, characterized in that: The weight portion of the silsesquioxane is 2-8 parts.

6. The polyamide composite material according to claim 1, characterized in that: The auxiliary agents include antioxidants and lubricants.

7. The polyamide composite material according to claim 6, characterized in that: The antioxidant comprises a compound of a hindered phenol antioxidant and a phosphite antioxidant; the lubricant comprises at least one of silicone, ester, amide, polyethylene, stearic acid and fatty acid lubricants.

8. The polyamide composite material according to claim 1, characterized in that: The toughening agent includes maleic anhydride grafts, and the maleic anhydride grafts include at least one of maleic anhydride grafted polyethylene, maleic anhydride grafted modified polyolefin elastomer, and maleic anhydride grafted ethylene propylene diene rubber.

9. The method for preparing the polyamide composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The components are mixed uniformly, and then melt-kneaded, extruded and granulated to obtain the polyamide composite material.

10. Use of the polyamide composite material according to any one of claims 1 to 8 in the preparation of hydrogen storage bottles and automotive wiring harnesses.

Citation Information

Patent Citations

  • Functional master batch for antisticking BOPA film and production process thereof

    CN102206412A

  • Polyamide resin composition, and molded article

    CN105143351A

  • Low-dielectric nano injection molding polyamide composite material and preparation method and application thereof

    CN112175387A

  • Microwave water-blocking and oxygen-blocking BOPP (Biaxially-oriented Polypropylene) film and preparation method thereof

    CN115847978A

  • Polyamide composite material as well as preparation method and application thereof

    CN116535845A